A randomized, placebo‐ and sitagliptin‐controlled trial of the safety and efficacy of omarigliptin, a once‐weekly dipeptidyl peptidase‐4 inhibitor, in Japanese patients with type 2 diabetes. Issue 11 (6th July 2017) - Gantz, Ira; Okamoto, Taro; Ito, Yuka; Okuyama, Kotoba; O'Neill, Edward A.; Kaufman, Keith D.; Engel, Samuel S.; Lai, Eseng; ,
Abstract : Aims: To assess the safety and efficacy of omarigliptin in Japanese patients with type 2 diabetes (T2D). Methods: In a 24‐week double‐blind trial, 414 patients with T2D were randomized to omarigliptin 25 mg once weekly, sitagliptin 50 mg once daily or placebo. The double‐blind period was followed by a 28‐week open‐label extension during which all patients received omarigliptin 25 mg once weekly. Efficacy endpoints were glycated haemoglobin (HbA1c), 2‐hour postprandial glucose (PPG) and fasting plasma glucose (FPG) levels. Results: After 24 weeks, the least squares (LS) mean change from baseline in HbA1c was −0.66% for omarigliptin, −0.65% for sitagliptin and 0.13% for placebo. The difference in LS mean for omarigliptin vs placebo was −0.80% ( P < .001). The difference in LS mean for omarigliptin vs sitagliptin was −0.02% (95% confidence interval −0.15, 0.12), which met the criterion for non‐inferiority to sitagliptin. Both active treatments provided significant reductions in FPG and 2‐hour PPG compared with placebo ( P < .001). Over the 24‐week double‐blind period, there were no clinically meaningful differences in the incidence rates of adverse events among the treatment groups. There was 1 episode of symptomatic hypoglycaemia in the sitagliptin group and none in the omarigliptin or placebo groups. In the 28‐week open‐label period, omarigliptin provided persistent improvements in glycaemic control without notable change in safety profile compared with the double‐blind period. Omarigliptin had no meaningful effect on body weight. Conclusions: In Japanese patients with T2D, omarigliptin 25 mg once weekly provided significant glucose‐lowering compared with placebo and was non‐inferior to sitagliptin 50 mg once daily. Omarigliptin was generally well tolerated for up to 52 weeks.